FORMATION OF THE MANAGEMENT STRATEGY OF TELECOMMUNICATION SERVICES ENTERPRISES ON THE BASIS OF DETERMINING THE VECTORS OF MANAGEMENT OF INTEGRATIVE DEVELOPMENT - Хаврова, Катерина; Голобородько, Альона (SWorldJournal, 2023)
In the context of digitalization and transformation of all processes, enterprise management should be based on the formation of sound development strategies that focus on the vectors of integrative development management. The article provides the author'